The Dynamics of illegal migration - Esteban, MA. Angelina Ignacio (KDI School, 2000)
The case study aimed to explore the factors which push and pull unskilled Filipino migrant workers to resort to illegal migration in the Republic of Korea. The research assumed that the policy of Korea of accepting unskilled foreign workers through the KFSMB Trainee Scheme serves as a “push” factor for workers to choose illegal work. The survey findings however showed that not only does this migration policy affects the propensity of workers to resort to illegal migration, rather, there is an interplay of various push and pull factors, the effects of which depend on the perception of the migrant workers on the costs and benefits he or she could get and at which stage of the migration process he or she is making a decision.
Thesis(Master) --KDI School:Master of Public Policy,2000